Applied theatre : international case studies and challenges for practice - Prendergast, Monica; Saxton, Juliana, 1933- (Bristol, UK ; Chicago : Intellect, 2009)
Applied Theatre is the first collection to assist practitioners and students in developing critical frameworks for their own community-based theatrical projects. The editors draw on thirty case studies in applied theatre from fifteen countries—covering a wide range of disciplines, from theatre studies to education, medicine, and law—and collect essential readings to provide a comprehensive survey of the field. Infused with a historical and theoretical overview of practical theatre, Applied Theatre offers clear developmental approaches and models for practical application.
Bibliografija: str. 207-219. - Kazalo
Access is available to the Yale community.
Keywords: Community theater -- Case studies; Community theater; Theater and society -- Case studies; Theater and society; kazalište u zajednici; kazalište i društvo; primjenjeno kazalište